Desa Konstitusi: Perwujudan nilai pancasila serta konstitusi dalam kehidupan masyarakatdan penyelenggaraan pemerintahan desa - Atmaja, Thomy Sastra; Jailani, Muhammad; Utami, Tri; Ayuni, Nina (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
The success of Mekar Sari Village as a role model in upholding the constitution and state ideology in people's lives must be appreciated and is interesting for in-depth study through research. As far as research has been conducted by researchers, research has never been conducted on constitutional villages in Mekar Sari Village, Sungai Raya District, Kubu Raya Regency. Even nationally, no articles or research results have been found regarding constitutional villages in Indonesia. The approach used in this research is a qualitative approach and descriptive method. From the research results, it was found that Mekar Sari Village has implemented constitutional values ​​and Pancasila values ​​in village government and community life. The values ​​of Pancasila and the Constitution that are realized include the values ​​of divinity, humanity, unity, democracy and justice.